A Fuzzy Set Analysis of Resources, Capabilities and University Spin-off Performance - Anna KWIOTKOWSKA (Communications of International Proceedings, 2020)
Prior literature does not sufficiently explain how different types of resources and capabilities contribute to perfomance of university spin-offs (USOs) nor does it clarify how these firms can combine different resources and capabilities to achieve superior performance outcomes. In addition, capturing performance outcomes of complex systems of interdependencies using commonly employed methods, such as regression models, is often difficult. Thus, this study employs a configurational approach, using fuzzy set Qualitative Comparative Analysis (fs/QCA), to analyze the resource and capability configurations of USOs that yield superior performance. The study finds no evidence of high-performing configurations without highly qualified human resources and shows that highly performing firms configure their resourecs and capabilities in three different ways. The results have implications for theory in the area of the initiation and growth of university spin-offs (USOs) as well as for configurational strategy research in general.
Keywords: Resources; Capabilities; University Spin-Off; Fuzzy Set Qualitative Comparative Analysis.